Implementing sustainable development strategies and initiatives in high consumption societies - Lafferty, William M., 1939-; Meadowcroft, James; Oxford eBooks (Oxford : Oxford University Press, 2000)
Examining how governments in the developed industrial world have responded to the challenge of sustainable development, this text shows that the concept has been integrated into governmental idiom in most jurisdictions.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Sustainable development; Sustainable development -- Case studies; Sustainable development -- Government policy; Electronic books